2024
DOI: 10.1038/s41591-024-02875-1
|View full text |Cite|
|
Sign up to set email alerts
|

Locoregional delivery of IL-13Rα2-targeting CAR-T cells in recurrent high-grade glioma: a phase 1 trial

Christine E. Brown,
Jonathan C. Hibbard,
Darya Alizadeh
et al.

Abstract: Chimeric antigen receptor T cell (CAR-T) therapy is an emerging strategy to improve treatment outcomes for recurrent high-grade glioma, a cancer that responds poorly to current therapies. Here we report a completed phase I trial evaluating IL-13Rα2-targeted CAR-T cells in 65 patients with recurrent high-grade glioma, the majority being recurrent glioblastoma (rGBM). Primary objectives were safety and feasibility, maximum tolerated dose/maximum feasible dose and a recommended phase 2 dose plan. Secondary object… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Fifty percent stable disease and two complete responses were induced by the CAR-T cell treatment MB-101 (Mustang Bio) in 65 heavily pretreated patients with recurrent and refractory, high-grade malignant glioma enrolled in a dose-escalation Phase 1 trial. 1 The regimen, which was tested with two routes of administration (intratumoral and intraventricular) and their combination, was well tolerated with no dose-limiting toxicities.…”
Section: Car-t Cell Therapy Induced Responses In Early Trial With Bra...mentioning
confidence: 99%
“…Fifty percent stable disease and two complete responses were induced by the CAR-T cell treatment MB-101 (Mustang Bio) in 65 heavily pretreated patients with recurrent and refractory, high-grade malignant glioma enrolled in a dose-escalation Phase 1 trial. 1 The regimen, which was tested with two routes of administration (intratumoral and intraventricular) and their combination, was well tolerated with no dose-limiting toxicities.…”
Section: Car-t Cell Therapy Induced Responses In Early Trial With Bra...mentioning
confidence: 99%
“…As the efficient homing of CAR-T-cells into the brain determines the efficacy of antitumor immunity, novel approaches to enhance the presence of CAR-T-cells are urgently needed. Locoregional delivery modalities, such as intraventricular (ICV), intracavitary (IC), or intratumor (IT) immunotherapy applications, have been successfully investigated in multiple human phase I GBM trials as an alternative to surmounting inherent biological barriers [15,18,22,50]. These targeted delivery routes hold the potential to achieve lower drug concentrations, thereby mitigating the risk of off-target toxicities.…”
Section: Alternative Delivery Routesmentioning
confidence: 99%
“…These targeted delivery routes hold the potential to achieve lower drug concentrations, thereby mitigating the risk of off-target toxicities. However, recent clinical trials have reported the presence of ICV/IT-administered CAR-T-cells in the periphery, and further investigations are needed to determine if local delivery can truly prevent off-target toxicities [22]. Furthermore, all techniques require invasive surgery.…”
Section: Alternative Delivery Routesmentioning
confidence: 99%
“…Nonetheless, finding the right combination of therapies and methods to activate the immune system such as through the use of adoptive cell therapies or therapeutic vaccines continues to hold promise in the search for effective treatments against this aggressive brain tumor [ 140 ]. For example, a phase 1 trial evaluating a locoregional delivery of IL-13Rα2-targeting chimeric antigen receptor (CAR)-T cells in recurrent high-grade glioblastomas showed promising clinical activity [ 141 ]. Similarly, intrathecal bivalent CAR-T cells targeting EGFR and IL13Rα2 in recurrent glioblastomas reported interim results showing manageable toxicity and encouraging progression-free survival [ 142 ].…”
Section: Alternative Interventionsmentioning
confidence: 99%